Factors Associated with Discussion of Disasters by Final Year High School Students: An International Cross-sectional Survey. Issue 4 (6th July 2015) - Codreanu, Tudor A.; Celenza, Antonio; Alabdulkarim, Ali A. Rahman
Abstract: Introduction: The effect on behavioral change of educational programs developed to reduce the community's disaster informational vulnerability is not known. This study describes the relationship of disaster education, age, sex, and country-specific characteristics with students discussing disasters with friends and family, a measure of proactive behavioral change in disaster preparedness. Methods: Three thousand eight hundred twenty-nine final year high school students were enrolled in an international, multi-center prospective, cross-sectional study using a pre-validated written questionnaire. In order to obtain information from different educational systems, from countries with different risk of exposure to disasters, and from countries with varied economic development status, students from Bahrain, Croatia, Cyprus, Egypt, Greece, Italy, Portugal, Romania, and Timor-Leste were surveyed. Logistic regression analyses examined the relationship between the likelihood of discussing disasters with friends and family (dependent variable) and a series of independent variables (age, gender, participation in school lessons about disasters, existence of a national disaster educational program, ability to list pertinent example of disasters, country's economic group, and disaster risk index) captured by the questionnaire or available as published data. Results: There was no statistically significant relationship between age, awareness of one's surroundings, planning for the future, and foreseeing consequences of events with discussions about potential hazards and risks with friends and/or family. The national educational budget did not have a statistically significant influence. Participants who lived in a low disaster risk and high income Organization for Economic Co-operation and Development (OECD) country were more likely to discuss disasters. While either school lessons or a national disaster education program had a unique, significant contribution to the model, neither had a better predictive utility. Conclusions: The predictors (national disaster program, school lessons, gender, ability to list examples of disasters, country's disaster risk index, and level of economic development), although significant, were not sufficient in predicting disaster discussions amongst teenagers. TA Codreanu, A Celenza, AAR Alabdulkarim .Factors associated with discussion of disasters by final year high school students: an international cross-sectional survey .Prehosp Disaster Med .2015 ;30 (4 ):1 –9 .